The conflict between the evidentiary evaluation criteria and the construction of a criminal process with a gender perspective - Ugarriza Landavery, Luciana Natalia (2021)
The author analyzes the problems facing the criminal process today in terms of witness-victim testimony in gender-based crimes that are the product of unbridled populism and citizen dissatisfaction. It is necessary to avoid any gender bias that could lead to irrational judicial decisions, without diminishing the procedural guarantees, especially those that assist those investigated.